2020
DOI: 10.1001/jama.2020.2783
|View full text |Cite
|
Sign up to set email alerts
|

Positive RT-PCR Test Results in Patients Recovered From COVID-19

Abstract: Purpose: The study is to describe the clinical characteristics, outcomes and follow-up of cancer patients with COVID-19. Methods: Clinical records, demographic data, signs and symptoms, laboratory results, cytokine pro les, chest CT scans, comorbidities, treatments, clinical outcomes, and RT-PCR of SARS-CoV-2 after discharge were retrospectively collected for fty-six cancer patients with laboratory-con rmed COVID-19 pneumonia who were admitted to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
1,209
5
27

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,203 publications
(1,288 citation statements)
references
References 5 publications
47
1,209
5
27
Order By: Relevance
“…Some COVID-19 patients who were considered recovered after symptoms resolved still carried detectable levels of SARS-CoV-2 for 5 to 13 days. 19 The naso-oropharyngeal specimens, collected from the third sampling of COVID-19 patients A and B, showed negative for SARS-CoV-2. However, their sputum specimens collected on the same day were tested positive.…”
Section: Clinical Manifestations Of Viral Respiratory Infections Rangmentioning
confidence: 94%
See 1 more Smart Citation
“…Some COVID-19 patients who were considered recovered after symptoms resolved still carried detectable levels of SARS-CoV-2 for 5 to 13 days. 19 The naso-oropharyngeal specimens, collected from the third sampling of COVID-19 patients A and B, showed negative for SARS-CoV-2. However, their sputum specimens collected on the same day were tested positive.…”
Section: Clinical Manifestations Of Viral Respiratory Infections Rangmentioning
confidence: 94%
“…The categorical variable was summarized as n/N (%), where N is the total number of patients with available data and continuous variable was summarized as mean (SD) or median (IQR). We assessed differences between COVID-19 and non-COVID- 19…”
Section: Methodsmentioning
confidence: 99%
“…According to data acquired from 4 Chinese patients who contracted COVID-19 and recovered, positive reverse transcriptaseepolymerase chain testing was still present at 5 to 13 days post infection and then on subsequent testing. 11 It is unclear whether this meant that they were continuously infectious or re-infected, but should give pause as to when recovering COVID-19 patients are safe to bring into a facility where rapid transmission of the virus to a susceptible population could occur. Further research into the post-infectious period will be Table 1 Practical Considerations for Reducing the Risk of Transmission in the Workplace 1.…”
Section: Maintain Health Care Infrastructurementioning
confidence: 99%
“…The COVID-19 virus is confirmed by testing for 2019-nCoV on respiratory material or serum by using reverse-transcription polymerase chain reaction (RT-PCR) analysis in accordance with the protocol established by the World Health Organization (WHO) (17). A second test or even more tests are needed because false negative RT-PCR results have been generated in 3% (5 of 167) patients with positive chest computed tomography (CT) findings (18) and in some patients who have recovered from COVID-19 disease (19). It is suggested that a chest CT is highly valuable for more sensitive, earlier diagnoses of COVID-19 (20) .…”
Section: What Interventional Radiologists Should Knowmentioning
confidence: 99%